Keeping the business going: SMEs and urban floods in Asian megacities. Issue 2 (April 2020) - Verrest, Hebe; Groennebaek, Laerke; Ghiselli, Adele; Berganton, Mariana
Abstract : Flooding presents one of the main risks to contemporary and future cities, especially those in coastal zones. Given the social–political nature and construction of urban flood risks, it is of crucial importance to understand how such risks are experienced and addressed, and by whom. This article aims to contribute to this by focusing on a particular actor, i.e. entrepreneurs of small and medium enterprises (SMEs). It asks how SMEs experience, perceive and address risks. This knowledge not only can help to improve flood governance by including one group's specific risks and opportunities but also provides new insights into how risk perceptions are constructed and shape subsequent strategies. The findings are based on a comparative study of SMEs in Jakarta, Metro Manila and Bangkok. Using a mixed methods design, the studies show that entrepreneurs distinguish between frequent everyday floods and scarce major floods, but only consider major floods a risk. The latter is explained by a combination of risk normalisation and incremental and independent everyday practices. Strategies aim at keeping the business going in the short run. There are substantial differences between medium and small companies. Finally, the research confirms that attention for SMEs in flood policies or support is nil.